Preparing for the crises after COVID-19: Systematic foresight as a tool for evidence-informed precautionary policy - Lars Brozus (Stiftung Wissenschaft und Politik (SWP), 2020)
Political decision-makers are regularly confronted with a large number of hypothetical crises. State and society expect them to make appropriate provisions to tackle these scenarios simultaneously. However, adequate preparation for all conceivable incidents in the future far exceeds the available resources. Decision-makers must therefore determine which of these imaginary crises should take priority. Factors such as the public visibility and likelihood of an expected crisis and the damage it is anticipated to cause play an important role in this decision. Also at play are analogy-based reasoning and political intuition. COVID-19 illustrates that these future heuristics entail significant decision-making risks. Despite many warnings about the consequences the spread of infectious diseases could have globally, hardly any state was adequately prepared. Taking credible predictions through systematic foresight into account would help decision-makers to set priorities for prevention that would be easier to explain and justify.
Keywords: 320